PENDIDIKAN SEKS BAGI ANAK SEKOLAH MINGGU USIA 7-14 TAHUN - Jefri Susanto Manik; Nadia Illsye Tular (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2022)
Seeing the number of acts of sexual violence against children which is increasing every year in Indonesia, the church should be aware of the importance of providing sex education to children from an early age. The church as an integral part of society and as the